Computational Fluid Dynamics Analysis of Gravitational Filter Based on Origami Concept (G-Filtro) Acted as Water Filtration Device in Water Tank - Zawawi M.H.; Mustafa Al Bakri Abdullah M.; Nazmi M.A.; Yusairah W.N.; Hassan N.H.; Shahira Jupri E.; Azam Afiq M.; Kamaruddin M.A.; Remy Rozainy Mohd Arif Zainol M.; Irfan A.R. (IOP Publishing Ltd, 2023)
Water is the most demanding resource in the world especially in the era of the rapid growth of population and development. Therefore, delivering good quality water to consumers is important for their security of lives. Gravitational Filter Based on Origami Concept (G-Filtro) is a water filtration device that will be placed in a water tank at the residential area before people consumed it for everyday used. The specialty of this device, it does not necessarily attach to any power source. The objective of this project is to design and develop 3D G-Filtro using 3D CAD software and CFD analysis is used to determine the efficiency of the G-Filtro by simulating and model the pressure, velocity and streamline. Based on the result, the maximum water velocity for simulation without the filter is 0.266 m/s and the maximum velocity for first and second designed filter are 0.254 m/s and 0.243 m/s respectively. From the CFD simulation, the G-Filtro can remove the contaminants in water tank efficiently. Hence, it is proven that G-Filtro can be added as a new water filtration device. Published under licence by IOP Publishing Ltd.